(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Prevention of hospital-acquired infections before, during and after surgery plays a role in determining hospital quality, reducing complications and 24-hour, 48-hour, and 6-month postoperative mortality. Study subjects and methods: The study was conducted on 30 medical staff and elderly patients with intertrochanteric and/or femoral neck fractures using descriptive methods and intervention. Study results: After the training on compliance with professional procedures according to Circular No. 19/2013/TT-BYT for medical staff in Nghe An Hospital for traumatology and orthopedics, the reduction rate of mortality and complications in patients with partial hip replacement and by internal fixing is after 24 hours and 48 hour surgery was 100.0%; surgical site infection decreased 35.8% after one month and decreased 100% after six months; and the mortality was reduced 100% after three months and 43.87% after six months.